THE CONNECTION OF THE ELEMENTAL COMPOSITION OF GRAINS AND STALKS OF THE MUNG BEAN PLANT TO THE SOIL - Kodirova (Mukhtorova) Shakhzodakhan Madaminjon qizi; Isaqov Muhammadjon Yunusovich; Muqimjonova Umidakhan Vakhobjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
The connection of the elemental composition of the STEM and grains of the mosh plant grown in the Besharik district with the elemental composition of the soil was discussed in this article on the basis of the results of neuron-activation analysis. Opinions were expressed on the distribution of macro-and microelements in the soil-stem-grain system.